Physical Exercise: Knowledge, attitude and participation of senior secondary school students of selected private schools in Ibadan North Local Government Area, Oyo State (Nigeria) - Fabunmi, Ayodeji; Jumbo, Ibigoni; Oloyede, Martins (Health Promotion & Physical Activity, 2019)
Background: Studies suggest that young adulthood is a critical time for physical exercise interventions. This study assessed knowledge, attitude and participation in physical exercise by students of privately owned secondary schools in Ibadan North East Local Government Area, Ibadan, Oyo State, Nigeria. Materials and methods: This study is a cross sectional survey. Informed consent was obtained from the schools and individual participants. Multi-stage sampling technique was used in selecting participants for the study. Each participant was guided in completing the questionnaire. Data on knowledge, attitude and participation in physical exercise was obtained from students. Data were analyzed using frequency, percentages and chi square. Results: Five hundred and sixty questionnaires were administered to respondents and 520 (92.9%) were completed and returned. Out of the 520 participants 258 (49.62%) were males and 262 (50.38%) were females. Out of 520 participants, 97.88% had good knowledge about physical exercise (49.23% males and 48.65% females). Out of 520 participants, 410 (78.85%) had good attitude towards physical exercise (40.96% males and 37.89% females). Male participants were better in knowledge and attitude than female participants. Participation in physical exercise was poor because participants were not putting in enough time in physical exercise. Conclusions: Boys had better knowledge about physical exercise and better attitude to physical exercise than girls. Girls actually participate more in physical exercise, though both boys and girls were not putting in enough time in participating in physical exercise. School curriculum that will encourage physical exercise should be adopted with more time allocated for physical exercises